The weak-form efficiency analysis of the Finnish stock market - Vanninen, Olli (My University, 2023)
In this thesis the weak-form efficiency of the Finnish stock market during the past 10 years is examined. The sample period is from 1.5.2013 to 30.4.2023. The full sample period is divided into three approximately equally long subperiods. The first subperiod is from 1.5.2013 to 1.9.2016, the second subperiod is from 2.9.2016 to 2.1.2020, and the third subperiod is from 3.1.2020 to 30.4.2023. Daily logarithmic returns are used in the thesis. The weak-form efficiency is examined with five types of tests, which are the autocorrelation test, the runs test, the variance ratio test, the day-of-the-week effect test, and the moving average trading rule test. In the thesis, tests for weak-form efficiency are conducted for OMXHGI and 9 individual stocks. 3 selected stocks are from small cap group, 3 selected stocks are from mid cap group, and 3 selected stocks are from large cap group. OMXHGI tracks the total return of the Finnish stock market. The empirical results of the thesis indicate that the overall Finnish stock market has been weak-form efficient in the past 10 years. The empirical results of the thesis also indicate that the weak-form efficiency has not increased or decreased significantly during the past 10 years. The empirical results of the thesis indicate that there is a real difference in the weak-form efficiency between different market capitalization groups. The empirical evidence indicates that the selected small cap stocks were not as weak-form efficient as the large and mid cap stocks. Surprisingly, selected mid cap stocks were more weak-form efficient than selected large cap stocks.

Tutkielmassa tutkitaan, onko Helsingin pörssi ollut heikosti tehokas viimeisen 10 vuoden aikana. Tutkielmassa tarkastellaan myös, onko Helsingin pörssin heikko tehokkuus kasvanut viimeisen 10 vuoden aikana. Tutkimusaineistona käytetään logaritmisia päivätuottoja ajalta 1.5.2013-30.4.2023. Tutkimusaineisto on jaettu kolmeen melkein yhtä suureen aikaperiodiin. Ensimmäinen aikaperiodi on 1.5.2013-1.9.2016, toinen aikaperiodi on 2.9.2016-2.1.2020 ja kolmas aikaperiodi on 3.1.2020-30.4.2023. Heikon tehokkuuden tutkimiseen käytetään viittä eri menetelmää, jotka ovat autokorrelaatio testi, juoksu testi, varianssi suhde testi, viikonpäivä anomalia testi, liukuvan keskiarvon testi. Tutkielmassa tutkittiin Helsingin pörssin tuottoindeksin ja yhdeksän osakkeen heikkoa tehokkuutta. Jokaiseen markkina-arvo kokoryhmään valittiin kolme osaketta. Tutkielman empiiriset tulokset osoittavat, että Helsingin pörssi on ollut heikosti tehokas viimeiset 10 vuotta. Tutkielman empiiriset tulokset osoittavat myös, että Helsingin pörssin heikko tehokkuus ei ole vahvistunut tai heikentynyt merkittävästi viimeisen 10 vuoden aikana. Lisäksi empiiriset tulokset osoittavat, että Helsingin pörssin pienyhtiöt ovat olleet heikommin heikosti tehokkaita kuin suuret ja keskisuuret yhtiöt. Yllättävästi valitut keskisuuret yhtiöt ovat olleet vahvemmin heikosti tehokkaita kuin suuret yhtiön.
Keywords: market efficiency, efficient market hypothesis, weak-form efficiency, Finnish stock market, markkinoiden tehokkuus, tehokkaiden markkinoiden hypoteesi, heikko tehokkuus, Suomen osakemarkkina